MANAGEMENT OF LEUKOPENIA ASSOCIATED WITH PARVOVIRUS GASTROENTERITIS IN A LABRADOR RETRIEVER PUPPY - A CASE REPORT - M. A. Ensha Lomiya; R. Raguvaran; Renu Motwani; Narayani Yadav; D. B. Mondal (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A four-month-old male Labrador retriever puppy was presented to Referral Veterinary Polyclinic, Indian Veterinary Research Institute with the history of anorexia, vomiting, haemorrhagic diarrhoea and signs of hypovolaemic shock. The case was diagnosed as parvovirus gastroenteritis by rapid antigen detection test. Shock was managed by infusion of polyionic isotonic fluid. Haematological examination revealed severe leukopenia with WBC count of 0.3×10³/µL, which was treated with administration of recombinant human granulocyte colony stimulating factor (Filgrastim) at 5 mcg/kg subcutaneously along with supportive therapy. Dog showed elevated WBC count and improvement in clinical signs after 48 h. Administration of granulocyte colony stimulating factor along with routine therapy enhanced the survivability in canine parvovirus gastroenteritis.